Price hedging for coffee, using the futures market - Barrios-Puente, Gerónimo; Galván-Manuel, Oscar; Pérez-Soto, Francisco; Sangerman-Jarquín, Dora Ma.; García-Sánchez, Roberto Carlos (Revista Mexicana de Ciencias Agrícolas, 2022)
The present work completed in January 2021 determined a price hedging model in the coffee futures markets. Following the analytical method, first, the behavior of the historical prices from January 2015 to December 2020 in the spot market and in the futures market was observed and analyzed, later using the standard deviation of the historical data, the volatility that exists in the futures market and its impact on the final price that producers receive for their harvest at the end of each production cycle was calculated. Applying the statistical theory of the binomial tree, the expected prices of the following three four-month periods are estimated, subsequently, the utility function of the producer is modeled, assuming it as the expectation of income and its variance, later the utility function of the producer is found and optimized to know the number of contracts that guarantees the hedging of the price of production. The results of this work suggest that the final income of the producer will depend directly on the production that is expected to have in each productive cycle, on the speculative game on the stock exchange (number of contracts) and on the forecast of the spot price at the time of the evaluation, finally, it is concluded that the producers could be motivated to use futures contracts as a hedging strategy, since even if the profits are not extraordinary, the income will always be higher when such hedging is used.